PHONO-GRAPHICAL AND MORPHOLOGICAL LEVEL IN STYLISTIC ANALYSIS (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article offers a comprehensive exploration of two fundamental levels—phonographical and morphological—in the realm of stylistic analysis. It begins by delineating the distinct features and significance of each level, elucidating how phonographical elements encompass sounds, rhythm, and acoustic patterns, while the morphological level delves into word structure, formation, and sentence construction. Moreover, the article provides vivid examples and explanations of various phonetic devices such as alliteration, consonance, and onomatopoeia, elucidating their roles in crafting stylistic effects. It further delves into prosody, rhyme, meter, and the nuanced aspects of spoken language, highlighting the interplay between phonetic elements and style. Additionally, the discussion on the morphological level encompasses word derivation, etymology, register, and sentence structure. The article underscores how word choice, prefixes, suffixes, and syntax significantly contribute to the overall style and impact of a text.